A History of Wildlife Laws in West Bengal - Bisht, S. S. (Indian Forester, 2001)
Scientific forest management started in Bengal on August 3, 1864 when the forest Department was established. But wildlife management was not a priority with the foresters in the beginning the British looked upon wild animals, birds and fish as 'game' or 'source of revenue'. They framed their early laws to protect the interests of the 'sportsmen' and the 'exchequer'. Some of the wildlife laws extended to areas outside the forests. Experience gained in the enforcement of these laws led to their amendment or replacement from time to time. Over the years the philosophy of wildlife management has changed and now principles of conservation, rather than those of sport and economics, govern the management of wild animals. This change has also influenced the laws pertaining to wildlife. Although most of the wildlife laws were framed by the Central Government, yet a notable exception remains the Rhinoceros Preservation Act passed by the Bengal Government in 1932. Enforcement of wildlife laws, particularly in areas outside the forests, is still a problem in West Bengal. The hunting and fishing rules framed in West Bengal under the Indian Forest Act, 1927 and the Wildlife (Protection) Act, 1972 have not been updated.